2016
DOI: 10.1002/jbm.a.35711
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of 3D porous SF/β‐TCP hybrid scaffolds for bone tissue reconstruction

Abstract: Bio-ceramic is a biomaterial actively studied in the field of bone tissue engineering. But, only certain ceramic materials can resolve the corrosion problem and possess the biological affinity of conventional metal biomaterials. Therefore, the recent development of composites of hybrid composites and polymers has been widely studied. In this study, we aimed to select the best scaffold of silk fibroin and β-TCP hybrid for bone tissue engineering. We fabricated three groups of scaffold such as SF (silk fibroin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…In this study, all the SF/SPI scaffolds fabricated through freeze-drying have an average pore size of more than 100 µm and proper porosities. With these pores, the amount of the incorporated β-TCP and GO nanoparticles can be significantly increased, which subsequently affects the hydrophobicity of the whole scaffolds [29,31]. When the β-TCP and GO nanoparticles appear on the surface of the pore walls, there form flake-like structures with sharp pore edges, which increase the surface roughness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, all the SF/SPI scaffolds fabricated through freeze-drying have an average pore size of more than 100 µm and proper porosities. With these pores, the amount of the incorporated β-TCP and GO nanoparticles can be significantly increased, which subsequently affects the hydrophobicity of the whole scaffolds [29,31]. When the β-TCP and GO nanoparticles appear on the surface of the pore walls, there form flake-like structures with sharp pore edges, which increase the surface roughness.…”
Section: Discussionmentioning
confidence: 99%
“…When SF is mixed with SPI, the hybrid characteristic peak becomes obviously broad, and moves to lower adsorption band (3400 cm −1 ), indicating that the two proteins are not only physically blended together, but interacted though hydrogen bonding. The SF/SPI/β-TCP and SF/SPI/GO/β-TCP scaffolds exhibit the characteristic peak at 660 cm −1 , which attributes to PO4 −3 groups [29,31,32]. The addition of GO enhances the intensity of -OH groups (3200 cm −1 to 3700 cm −1 ) with broader band, representing the intermolecular hydrogen bonding in the scaffold.…”
Section: Chemical Constituents Of the Sf/spi-based Composite Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 105 papers [ 54 158 ] were included in the systematic analysis. The data indicated that micro-CT was used only qualitatively in around 15% of the papers [ 63 , 74 , 75 , 79 , 95 , 102 , 106 , 108 , 112 , 116 , 122 , 129 , 133 , 146 , 149 , 158 ], and only quantitatively in 9.5% of the papers [ 55 , 78 , 83 , 85 , 98 , 111 , 125 , 131 , 137 , 155 ]. Micro-CT was used both qualitatively and quantitatively in the rest of the papers [ 54 , 56 62 , 64 73 , 76 , 77 , 80 82 , 84 , 86 94 , 96 , 97 , 99 101 , 103 105 , 107 , 109 , 110 , 113 115 , 117 121 , 123 , 124 , 126 128 , 130 , 132 , 134 136 , 138 – 145 , 147 , 148 ,…”
Section: Introductionmentioning
confidence: 99%
“…The manufacture of scaffolds mimicking the extracellular bone matrix, which is composed of collagen fibers, calcium, phosphorus, and other minerals, has not yet been resolved [5][6][7]. Scaffolds made from polymer fibers have many of the characteristics necessary for the adhesion, proliferation, and differentiation of mesenchymal stem cells and osteoblasts [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%